Just React! : learn React the react way - Narayn, Hari (Apress, 2022)
Here is your perfect companion for learning about and developing React applications. This book introduces concepts innovatively, using real-world examples based on the most recommended practices to help you establish a firm foundation. This comprehensive approach provides a strong focus on building components by using React hooks. You'll begin by learning web fundamentals, next-generation JavaScript, and how React fits into this. In the chapters that follow, you'll build a React application from scratch and learn about JSX, components, props, state management, prop drilling, context, and lifecycle events. Along the way you'll build a multi-component app and see how the components interact. Debugging and styling React applications are also discussed. You'll then take an in depth look at React hooks and see how to create a custom hook. There is also a penultimate chapter that explores important concepts such as routing and authentication. The book concludes with a review of some exciting features in the upcoming release of React 18. After reading Just React you will be equipped with the skills necessary to build complex web and mobile user interfaces using this flexible JavaScript library. What You'll Learn Examine the details of modern React concepts through example projects Set up your own React project Debug and style React components Take a look at routing, authentication, HTTP requests, Redux, and the new features of React 18 Who This Book Is For Web developers, React developers, and JavaScript developers.